THE IMPORTANCE OF EDUCATION IN THE DEVELOPMENT OF PERSONAL SPIRITUAL NEEDS (Universal International Scientific Journal, 2026)
The article analyzes the need for education and training to satisfy the spiritual needs of the individual, the formation of skills and abilities based on theoretical spiritual and moral knowledge acquired by students in the educational process, making decisions on moral qualities in positive content and issues of improving spiritual culture.
Keywords: The concepts of man, human spirituality, spiritual need, educational process, upbringing, reader, knowledge, ability to form.